A Phage-Like Plasmid Carrying blaKPC-2 Gene in Carbapenem-Resistant Pseudomonas aeruginosa - Galetti, Renata; Andrade, Leonardo Neves; Varani, Alessandro M.; Darini, Ana Lúcia Costa (Frontiers in Microbiology, 2019)
Background: Lateral gene transfer plays a central role in the dissemination of carbapenem resistance in bacterial pathogens associated with nosocomial infections, mainly Enterobacteriaceae and Pseudomonas aeruginosa. Despite their clinical significance, there is little information regarding the mobile genetic elements and mechanism of acquisition and propagation of lateral genes in P. aeruginosa, and they remain largely unknown. Objectives: The present study characterized the genetic context of blaKCP-2 in carbapenem-resistant P. aeruginosa strain BH9. Methods: P. aeruginosa BH9 sequencing was performed using the long-read PacBio SMRT platform and the Ion Proton System. De novo assembly was carried out using the SMRT pipeline and Canu, and gene prediction and annotation were performed using Prokka and RAST. Results: P. aeruginosa BH9 exhibited a 7.1 Mb circular chromosome. However, the blaKPC-2 gene is harbored in an additional contig encoded by plasmid pBH6 from P. aeruginosa strain BH6 and several phage-related genes. Further analysis revealed that the beginning and end of the contig contain identical sequences, supporting a circular plasmid structure. This structure spans 41,087 bp, exhibiting all the Mu-like phage landmarks. In addition, 5-bp direct repeats (GGATG) flanking the pBH6 ends were found, strongly indicating integration of the Mu-like phage into the pBH6 plasmid. Mu phages are commonly found in P. aeruginosa. However, to the author’s best knowledge, they have never been reported as integrated into plasmids. Conclusions: pBH6 captured the Mu-like Phage BH9, creating a co-integrate pBH6::Phage BH9, and this phage-plasmid complex may represent novel case of a phage-like plasmid.